Proinflammatory Cytokines and C-Reactive Protein in Uveitis Associated with Behçet's Disease - Marina Mesquida; Blanca Molins; Victor Llorenç; Maite Sainz de la Maza; María Victoria Hernandez; Gerard Espinosa; Alfredo Adán (Hindawi Limited, 2014)
The aim of the present study was to determine the serum cytokine profile and levels of high sensitivity C-reactive protein (hsCRP) in patients with uveitis associated with Behçet's disease (BD) and to compare them with those obtained from healthy control subjects. We determined the serum concentration of interferon-γ (IFN-γ), interleukin-1β (IL-1β), IL-12p70, IL-17A, tumor necrosis factor-α (TNF-α), and hsCRP in 13 patients with active uveitis associated to BD, 24 inactive BD patients, and 20 controls. In a subgroup of 10 active patients, a second serum sample was obtained when the disease was inactive. Cytokine profiles and hsCRP levels were correlated with disease activity, severity, complications, and visual outcome. Levels of IFN-γ and TNF-α were significantly increased in patients with active uveitis associated to BD compared to controls (P<0.05). IFN-γ, TNF-α, and hsCRP were significantly higher during active uveitis associated to BD compared to inactive disease (P<0.05). Furthermore, IL-17A was significantly increased in patients with active BD without pharmacological treatment compared to controls (P<0.05). No significant correlations were found with specific cytokine profiles and disease severity, visual outcome, or complications. In summary, increased serum levels of IFN-γ, TNF-α, IL-17A, and hsCRP were associated with active uveitis associated with BD and might serve as markers of disease activity.